An approximation of occupational lifetime UVR exposure: algorithm for retrospective assessment and current measurements. (April 2016) - Wittlich, M.; Westerhausen, S.; Kleinespel, P.; Rifer, G.; Stöppelmann, W.
Abstract: Background: Since non‐melanoma skin cancer (NMSC) has been adopted as an occupational disease in Germany, in any single suspected case a retrospective estimation of the outdoor workers' occupational UVR exposure is mandatory. Objective: The aim of this study was to introduce the recent German standard procedure as a mathematical algorithm for retrospectively estimating individual occupational UVR lifetime exposure. In addition, to present results of exemplary on‐the‐job UVR dosimetry measurements on outdoor workers during their various occupational activities. These dosimetry data form the basis of the mathematical model for UVR exposure estimation. Methods: On‐the‐job personal dosimetry in various outdoor professions was conducted using the GENESIS‐UV measurement system for individual UVA/UVB exposure assessment. The algorithm is derived from the results of these pars pro toto exemplary dosimetric measurements. For retrospective UVR lifetime estimation in suspected cases, a standardized patient interview serves as input and delivers all necessary information for using the algorithm. With defined factors, an individual adjustment is achieved. Results: Inserting the data derived from the patient interview, the algorithm shows to be feasible to calculate the lifetime UVR exposure retrospectively. As an example, an assessment for a 67‐year‐old agricultural teacher with three distinct occupational UVR exposure episodes is calculated. Conclusion: The presented algorithm has proven to facilitate the anamnestic procedure to estimate the lifetime UVR dose of exposed outdoor workers. With a recently developed computer‐based tool, standardized interviews of suspected workers with NMSC become simple. UVR dose as well as matching of requirements for recognition as an occupational disease in an individual worker are calculated automatically. Furthermore, with ongoing on‐the‐job measurements, a database is created to continuously adjust the algorithm's reference values for the various UVR‐exposed occupations. In addition, a job exposure matrix UVA/UVB is created as a pivotal tool for improved health and safety of outdoor workplaces and prevention of occupational actinic damage to the skin.